Weak Electrostatic Interactions with Bisphosphine Ligands Facilitate Reductive Elimination of PhCF3 from Pd(II) Complexes. Issue 5 (13th January 2023) - Gao, Han; Hu, Lingfei; Hu, Yanlei; Lv, Xiangying; Wu, Yan‐Bo; Lu, Gang
Abstract: The origins of ligand effects on PhCF3 reductive elimination from Pd II complexes were computationally investigated by using energy decomposition analysis. The results indicate weak electrostatic interactions between ligands and Ph−Pd−CF3 lead to small barriers of PhCF3 reductive elimination. Two major factors affecting the electrostatic interactions are identified. Abstract : Energy decomposition analysis reveals that weak electrostatic interactions between bisphosphine ligands and Ph−Pd−CF3 result in high reactivity of PhCF3 reductive elimination from Pd(II) complexes.